A path to renal transplantation in Nepal - Enns, J; Aryal, G (Journal of Pathology of Nepal, 2011)
End Stage Renal Disease affects many people in the world. There are three methods of renal replacement therapy available to patients: Continuous ambulatory peritoneal dialysis, haemodialysis and transplantation. Transplantation is the most viable and cost effective form of renal replacement therapy that is available for these patients. There are 3 factors required to help ensure a successful renal transplantation program: A well legislated donor and recipient program, Human Leukocyte Antigen testing (pre and post transplant), as well as a post transplant follow up program. Keywords: Renal Transplant; South Asia; Nepal; Human Leukocyte Antigen DOI: 10.3126/jpn.v1i1.4453 Journal of Pathology of Nepal (2011) Vol.1, 52-55